JAKARTA YOUTH’S LIFESTYLE AND FASHION ON TOP OF KOREAN WAVE - Putri Syifa Humaira; Annisa Nurwanda Putri; Pratiwi; Jerry Heikal (Jurnal Media Akademik (JMA), 2024)
The Korean Wave, or the cultural wave originating from Korea, became a significant phenomenon in Indonesia in the recent years. Its popularity, especially among the youth, surged alongside the emergence of Korean dramas and K-Pop music. Given this phenomenon, the researchers were interested in examining how the Korean Wave influences shared lifestyle and fashion choices of the young people, particularly in Jakarta, one of the cities with the largest K-Pop fan base in Indonesia. This study employed a qualitative method with an ethnographic approach. The data were collected through observations and interviews with five respondents who are K-Pop and Korean Drama enthusiasts in Jakarta. The findings indicate that although each respondent has a unique styles and preferences, they share similar preferences in lifestyle and fashion due to the influence of the Korean Wave, such as get highly motivated, be more expressive, more realistic, and more confident. This influence is supported by the dissemination of information related to Korean lifestyle and fashion through social media.